THE DISCOURSE OF WHITE SUPREMACY TOWARDS CONFORMATION OF BLACK IDEAL MASCULINITY OF ALFA NDIAYE’S ATTRIBUTES IN DAVID DIOP’S NOVEL AT NIGHT ALL BLOOD IS BLACK - Akbar, Rifqi; Agustin, Nerry (Universitas Islam Sumatera Utara (UISU), 2023)
Colonialism is one of the events of colonization of Europeans or Western nations to a nation or continent with inferior value to its customs, intellectuality, and marginalization. It results in the distingency of social structures that experience racial inequality and discrimination, including black people. White supremacy perpetuates an ideology that can take away the human rights of blacks, especially the ideal identity of masculinity, the black men. Black men are represented as beasts, combat-ready pioneers, obedient slaves, and so on. This representation becomes a construction of an ideological discourse that marginalizes black people. This discourse affects psychological and social dualism and intersectionalism that rests on resistance to white supremacy. This study aims to reveal the discourse of the identity of idealistic masculinity in black men. The method used is descriptive-qualitative. This method is employed in relating the problems that occur to Alfa Ndiaye who experiences the traumatic experience of the death of his best friend in his life journey while tracing racial equality between the countries of Francophone, France-Africa (Senegal). This study uses intersectional, masculinity, and racial studies. The material object is the novel At Night All Blood is Black by David Diop. In contrast, the formal object is ideology's effect in identifying masculinity's attributes in black people, especially in the main character, Alfa Ndiaye. Thus, white hegemony always uses various ways to make the ‘wounded masculinity’ of Ndiaye feel pressured and it is considered that their savagery is beneficial for Captain Armand in raising French independence.